Reconfiguring crystal and electronic structures of MoS2 by substitutional doping - Joonki Suh (Nature Portfolio, 2018)
Substitutional doping is well-established in traditional semiconductors but has not been extensively explored in two-dimensional semiconductors. Here, the authors investigate the structural and electronic effects of Nb doping in MoS2 crystals.